1995
DOI: 10.3171/jns.1995.83.5.0838
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of carotid-cavernous sinus fistulas using a superior ophthalmic vein approach

Abstract: The authors describe the method and results of treatment of 12 consecutive patients with carotid-cavernous sinus fistulas (CCFs). Treatment was by embolization via a transvenous approach through the superior ophthalmic vein (SOV). The CCFs (two direct and 10 dural) had previously been treated unsuccessfully or, for mechanical reasons, could not be treated by the standard techniques of endoarterial balloon occlusion, particle or glue embolization of feeding vessels from one or both external carotid arteries, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
2
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(71 citation statements)
references
References 11 publications
1
66
2
1
Order By: Relevance
“…We think that our results compare quite favorably with recent studies of endovascular treatment of patients with cavernous sinus DAVFs. Miller et al reported the results of ten patients with Types B to D cavernous sinus DAVFs treated transvenously, several patients (number not specified) experienced transient ocular motor dysfuncion; one patient developed new VI cranial nerve weakness, which did not resolve and necessitated later strabismus surgery 20 . Roy and Raymond treated 12 patients with cavernous sinus DAVFs treated with either a transarterial, transvenous or combined endovascular approach, transient VI cranial nerve weakness was observed for five patients (42%); one patient experienced permanent abducens palsy 25 .…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We think that our results compare quite favorably with recent studies of endovascular treatment of patients with cavernous sinus DAVFs. Miller et al reported the results of ten patients with Types B to D cavernous sinus DAVFs treated transvenously, several patients (number not specified) experienced transient ocular motor dysfuncion; one patient developed new VI cranial nerve weakness, which did not resolve and necessitated later strabismus surgery 20 . Roy and Raymond treated 12 patients with cavernous sinus DAVFs treated with either a transarterial, transvenous or combined endovascular approach, transient VI cranial nerve weakness was observed for five patients (42%); one patient experienced permanent abducens palsy 25 .…”
Section: Complicationsmentioning
confidence: 99%
“…Endovascular techniques have become the most common treatment for patients with symptomatic cavernous sinus DAVFs that do not spontaneously resolve, because of the high rates of cure after emboliza-A B C D tion 2,6,10,14,24 . However, embolization of cavernous sinus DAVFs has been reported to cause at least temporary ophthalmoplegia in eight to 50% of patients 1,20 , and recanalization of embolized DAVFs is well documented 26 . Direct surgical treatment is difficult and is associated with high rates of postoperative cranial nerve deficits 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Endovascular techniques are the most commonly used treatment for patients with symptomatic cDAVFs that do not spontaneously resolve. However, recent investigations have indicated that embolization of cDAVFs is not a thoroughly safe procedure and may also be related to temporary ophthalmoplegia [10][11][12] . Not only are the surgical approaches difficult, but cDAVF embolization has a high rate of postoperative cranial nerve deficit and associated occlusion of the ICA 13 .…”
Section: Procedures and Approachesmentioning
confidence: 99%
“…Both transarterial 4,5 and transvenous 1-3 approaches have been adopted. The transvenous approach has been shown by several studies to have a better clinical outcome and anatomical cure rate [5][6][7][8][9][10] . Among the transvenous approaches, IPS and facial vein through SOV 2 are the two most widely described routes of choice.…”
Section: Discussionmentioning
confidence: 99%
“…The transvenous approach is preferred due to higher clinical and anatomical cure rate [5][6][7][8][9][10] . There are various transvenous routes in embolization of DCCF 11 .…”
Section: Introductionmentioning
confidence: 99%